Readiness and Diagnosis in Counseling and Psychotherapy - Sekar Kurnia Rahmadani; Mudjiran; Yeni Karneli (Journal Of Psychology, Counseling And Education, 2024)
Readiness is an important factor in the success of the counseling process. In counseling there are several factors that influence the counselor's readiness including; concept abilities/strengths and in giving/receiving information about oneself. Methods for preparing clients: discussing specifically the importance of carrying out counseling on problems experienced by clients, motivating clients to look for/contact institutions/agents who can provide assistance related to the problems they are experiencing, making referrals/handovers in cases where the problems they face require professional assistance. specifically, providing information related to client problems, motivating clients to take specific "education" and intensify problems. In the medical world, diagnosis means finding a hypothesis from the observed symptoms, not much different from that definition. Diagnosis in counseling aims to make a temporary hypothesis about the problem experienced by the client. This can be observed through the client's behavior, expressions, explanation of the problems they are experiencing. With a hypothesis, the counselor can more easily understand the client so that he finds the right technique/method to alleviate the client's problems and direct the client's independence.